(untitled) (Salud, Arte y Cuidado, 2025)
Incontinentia pigmenti (IP) is a rare genodermatosis (0.7 per 100.000 births). It is characterized by a multisystemic affectation with a highly variable phenotype. The most common clinical manifestations are dermatological, neurological, ophthalmic and dental. The cutaneous alterations, markers of this entity, appear early, following a characteristic pattern of Blaschko’s lines. 4 sequential appearance phases are defined: vesicular, verrocous, hyperpigmentation and hypopigmentation phases, extracutaneous involvement defines functional prognosis, and is the cause of irreversible sequelae that determines the severity the disease. IP is an X-linked dominant disorder caused by a mutation in the NEMO gene. We describe a one-month and 26-years-old female infant is presented, who showed hyperpigmented skin lesions incidentally, noticed by her mother since 23rd day old, grouped vesicle-like skin lesions with linear distribution on the ring finger and the middle finger, both knees and right external malleolus, which after two weeks evolve into brownish verrocous lesions leaving hyperchromic spots following the Blaschko’s lines. The clinic diagnosis is made using 2 greater criteria: typical neonatal eruption and hyperpigmentation that follows the Blaschko’s lines, 2 lower criteria: strabismus and alopecia; it finds the 3° stage hyperpigmentation to incontinentia pigmenti. Biopsy was postponed due to the patient age and not having authorization of the parents